The Order and Chaos in Human Relationships: Objective Grounds and the Ways of Harmonization - Shapoval, V. M.; Шаповал, В. М.; Tolstov, I. V.; Толстов, І. В. (Anthropological Measurements of Philosophical Research. – 2024. – № 25. – P. 68-76, 2024)
Purpose. This article aims to provide a philosophical analysis of disharmonious relations between people in society, to reveal the causes of existing conflicts and to find ways to reduce the manifestations of chaos in human relations. Theoretical basis of the article is socio-cultural anthropology, the principles of the unity of the historical and logical, the ascent from the abstract to the concrete, the unity of analysis and synthesis. To solve the tasks set, authors also used the principles of objectivity, systematicity, and comprehensive development. Originality. The article goes beyond one-sided views on the relationship between people in society, reveals the causes of existing conflicts from a philosophical perspective and searches for ways to reduce chaosogenic manifestations in society. It is assumed that chaos and order in human relations arise not only due to the contradictory interaction between the fundamental components of the Universe – matter and energy, but also due to a lack of understanding of the laws of information use. Therefore, without the discovery and rational use of the basic laws and principles governing the functioning of information in the Universe, it is impossible to overcome chaos in human relations. Conclusions. Given the profound impact of information on human relations, it is possible to help reduce the manifestations of chaos in human relationships. The proper handling of information, along with the rational use of matter and energy, is crucial for overcoming the current state of disharmony and creating a more favourable and orderly future for humanity. Thus, the vector of harmonisation of human relations lies in the plane of comprehensive knowledge of mass-energy and information processes occurring in the Universe, focusing not on subjective, ill-considered short-term goals, but submitting to them for consistent inclusion in these processes.

Ця стаття має на меті провести філософський аналіз дисгармонійних стосунків між людьми в суспільстві, виявити причини існуючих конфліктів і знайти шляхи зменшення проявів хаосу у людських стосунках.

Целью данной статьи является философский анализ дисгармоничных отношений между людьми в обществе, выявление причин существующих конфликтов и поиск путей уменьшения проявлений хаоса в человеческих отношениях.
Keywords: Україна; publikatsii u WoS; human; universe; society; order and chaos; information; regulation of human relationships; людина; всесвіт; суспільство; порядок і хаос; інформація; регулювання людських стосунків; человек; вселенная; общество; порядок и хаос; информация; регулирование человеческих отношений